Competitive Strategy, Competitive Advantages, dan Marketing Performance pada E-Commerce Shopee Indonesia - Hermawan, Eric (Siber Nusantara Publisher, 2023)
Abstract: in the era of the industrial revolution 4.0 as facilitating all economic and business activities globally. Moreover, buying and selling activities that are usually offered conventionally are now made digitally, which is called E-commerce. E-commerce began to develop in Indonesia in 1999 with a buying and selling platform, namely Kaskus. At first, the emergence of e-commerce was not fully accepted by the public, due to various factors, for example the quality of the products offered. Until 2009 various kinds of e-commerce platforms began to develop in Indonesia, one of which was Shopee. To deal with the existing Competitive Advantages, Shopee uses several Competitive Strategies to analyze the advantages that exist in the Marketing Performance, Cost Leadership, Alliance, and Innovation strategies. Abstrak: di era revolusi industri 4.0 ini sebagai memudahkan segala kegiatan ekonomi dan bisnis secara global. Terlebih kegiatan jual beli yang biasanya ditawarkan secara konvensional, kini dibuat secara digital yaitu disebut E-commerce. E-commerce mulai berkembang di Indonesia pada tahun 1999 dengan platform jual beli yaitu Kaskus. Pada awal nya kemunculan e-commerce belum dapat diterima sepenuhnya oleh masyarakat, karena berbagai faktor misalnya kualitas produk yang ditawarkan. Hingga pada tahun 2009 mulai berkembang berbagai macam platform e-commerce di Indonesia, salah satunya Shopee. Untuk menghadapi Competitive Advantages yang ada, maka Shopee menggunakan beberapa Competitive Strategy guna menganalisis kelebihan yang ada pada strategi Marketing Performance, Cost Leadership, Alliance, dan Innovation.